International Financial Statistics, September 2017. (International Financial Statistics; International Financial Statistics ;, 2017)
This paper discusses the complete set of updated country notes is accessible from the IFS Online Service internet site (in the Metadata tab), and appear on the DVD-ROM edition of IFS under the Publications tab. A print edition of Country Notes may be ordered separately by subscribers of the DVD-ROM. The sources for the unit labor cost data are the OECD Analytical Database (quarterly unit labor cost in manufacturing) and IMF staff (annual data interpolated into higher frequencies). Euro area unit labor cost is used as a proxy for a number of economies for which data are unavailable: Cyprus, Czech Republic, Estonia, Latvia, Lithuania, Malta, and Slovak Republic. For manufactured goods, trade by type of good and market is distinguished in the database. For primary products, the weights assigned depend principally on a country's role as a global supplier or buyer of the product. Trade in crude petroleum, petroleum, and other energy products are excluded. For some countries that heavily depend on tourism, bilateral exports of tourism services averaged over 2004-2006 are also included in calculating the competitiveness weights.